Impacts of the Covid-19 pandemic on the mental health of health professionals and its relevance to stress levels as psychosocial change: an integrative literature review - Silva, Maria Amanda Oliveira da; Costa, Maria da Conceição Freitas da; Silva, Thaylon Menezes Ferreira da; Nogueira, José Eriverton Sousa; Sousa, Jady Júlia Patrício de; Rodrigues, Shara Teixeira Belarmino; Neves, Maria Galba das; Rodrigues, José Auberlanio Lima; Mesquita, Natanael Carvalho de; Sousa, Zildenilson da Silva; Silva Júnior, José Nilton da; Silva, Willian Ferreira da; et al. (Revista de Casos e Consultoria, 2021)
With the overcrowding in the hospital environment, the increase in the number of deaths from Sars-CoV-2 infection, ineffective treatments and the high contagion curve, health professionals working on the front lines in the fight against the new coronavirus (Covid-19) had your mental health affected by the pandemic. Therefore, this work aims at the psychological effects caused by covid-19 in health professionals working in the fight against infection. This is an integrative, descriptive exploratory review study. For its realization, descriptors registered in the Medical Subject Headings (MeSH) and Descriptors in Health Sciences (DeCS) were interconnected through “AND / OR” and communicated in PubMed / Medline, LILACS and BDENF. As a result, it was observed that with the advancement of coronavirus infection, several professionals from the multidisciplinary team of public and private hospitals, especially those working in Intensive Care Units (ICU), were psychologically affected. Professionals had a great demand in patient care, which consequently caused damage to their mental health. Stress, fear and insecurity were the effects most reported by professionals, especially those in Nursing. Based on the findings, further qualified studies are needed to reduce the long-term psychological effects of Covid-19 on healthcare professionals working on the front line of the infection.